Pengaruh Brand Association Terhadap Consumer Response Pada Produk Louis Vuitton Di Surabaya - Angela Stephani; Indarini Indarini; Christina Rahardja Honantha (Universitas Airlangga, 2008)
Louis Vuitton is known with initial LV and also a brand that affected consumer in decision making. Brand Association are attributes linked to the brand by customers that is determined with the guarantee function, the personal identification function, the social identification function, dan the status function. Consumer response is an effort to satisfy a drive. Reaction evoked by a stimulus consumer response, which it is determined with willingness to pay a price premium for the brand, willingness to accept brand extentions, dan willingness to recommend the brand to other. This research aim to test the effect of brand association of LV to consumer response with linier regression. The result shows that brand association of LV affect consumer response significantly.